The Incidence of Dysarrhythmias, Their Types and Outcomes in Patients Hospitalized with COVID -19 - Kamil Faeq , Abdulsatar (Diyala Journal of Medicine, 2021)
Background: COVID-19 infection started in China and became a pandemic, the SARS-CoV-2 virus mainly affects the respiratory system but can insult the cardiovascular system as well, higher rate of cardiac arrhythmias noted during the pandemic, and many studies showed that COVID-19 (especially hospitalized patients) can develop different types of arrhythmias which cause higher mortality rate. Objective: To assess the incidence of dysrhythmias and their types and outcomes in hospitalized patients with COVID-19 in Erbil city. Patients and Methods: Patients with documented COVID-19 infection admitted in Erbil Teaching Hospital respiratory care unit and coronary care unit from 1-8-2020 to 30-10-2020 had been included (255 patients) in this cross-sectional study, demographic data, and outcomes were reported, the ECG analyzed by cardiologists and the type of arrhythmia documented. Results: Mean age was 47±12 years, 61% of the patients were male, 25% of them had previous cardiac diseases, 20% diabetes, 16% multiple comorbidities, 8% hypertension, 8% obesity and 23% had no comorbidities, 20.7% of in-hospital patients developed dysrhythmias, 5.9% of them developed sinus tachycardia, 4.7% atrial fibrillation, 3.9% ventricular premature contractions, 2% ventricular fibrillation, 1.9% ventricular tachycardia and 1.9% heart blocks. Most of the patients who developed ventricular arrhythmias, atrial fibrillation, and heart block had previous comorbidities 82%, 62%, and 80% respectively. Arrhythmias caused a higher in-hospital mortality rate (39.6% versus 21.7%) especially among male patients (mortality rate in male patients 43% compared with female patients 33%). Conclusion: Most of the admitted cases were male. Most of them had comorbidities especially previous cardiac diseases. Sinus tachycardia, atrial fibrillation, and ventricular extra-systoles were the most frequent arrhythmias. The mortality rate was increased by arrhythmias mainly in male patients.